IMPLEMENTASI NILAI-NILAI PANCASILA SEBAGAI IDEOLOGI NEGARA DALAM KEHIDUPAN MASYARAKAT DI ERA GLOBALISASI - Keren Mawar Eliza; Silviana Sari, Shalsabila Hellenia, Fathi Tianasati, Zainudin Hasan (INTELIGENSIA MEDIA, 2024)
Pancasila is the foundation of the Indonesian state which is used as a guideline for the life of every Indonesian citizen Pancasila and Globalization are two things that are mutually sustainable. As time progresses, society's way of life begins to experience various changes which directly affect the way of life of a nation. The impact that occurs is enormous on various aspects of human life at all levels of society. On this occasion, the research aims to raise ideas regarding the importance of implementing Pancasila values in order to create a strong unity in the midstof rapid globalization which gives rise to various challenges and threats to the moral life of a nation. Apart from that, this research also raises the idea of the importance of the Pancasila ideology as a guideline in the life of society, nation and state by the Indonesian people. There are many noble values that can be re-implemented to unite the nation, whose society is very diverse starting from cultural background, ethnicity, religion, belief, language, and others. This article aims to analyze current threats that affect people's daily lives by reviewing the noble values of Pancasila with consideration of rationality in overcoming problems in the era of globalization